A bilayered scaffold with segregated hydrophilicity-hydrophobicity enables reconstruction of goat hierarchical temporomandibular joint condyle cartilage. (February 2021) - Yu, Xi; Hu, Yihui; Zou, Luxiang; Yan, Shifeng; Zhu, Huimin; Zhang, Kunxi; Liu, Wenguang; He, Dongmei; Yin, Jingbo
Abstract: Temporomandibular joint (TMJ) supports chewing, talking or other daily oral activities. So far, it still remains a great challenge to treat the defected TMJ condyle cartilage through tissue engineering technology. Herein, a bilayered scaffold is designed to fully reconstruct the different cartilage matrices of TMJ condyle under same induction condition. The bilayered scaffold with segregated hydrophobicity-hydrophilicity in top and bottom layer is prepared from a low and high content of polyethylene glycol (PEG) crosslinked poly (L-glutamic acid)- g -polycaprolactone (PLGA- g -PCL). The hydrophobic aggregates in top layer support the adhesion and spread of bone mesenchymal stem cells (BMSCs), thus inducing the differentation towards fibrocartilage; while aggregates (spheroids) are formed on the hydrophlic bottom layer, showing a preferable hyaline differentiation pathway under same chondrogenic induction in vitro . After 14 d in vitro induction, the scaffold/BMSCs construct is implanted in goat TMJ condyle defects. The post-operative outcome after 2 months demonstrates that the defects are fully covered by neo-cartilage. And the regenerated hierarchical TMJ condyle cartilage perfectly consist of ordered fibrocartilage and hyaline cartilage, which is same as natural condyle cartilage. These results corroborate that this bilayered scaffold with segregated hydrophilicity-hydrophobicity carrying induced BMSCs is a promising for treatment of TMJ condyle cartilage defects. Graphical abstract: Image, graphical abstract